γ-Irradiation of Thymine Dimers in Aqueous Solution - Deering, R. A. (1968)
Thymine dimers were irradiated in aqueous solution with (60)Co γ-rays in N(2) or O(2). Thymine and unidentified non-UV-absorbing products appeared. The thymine was identified by spectrophotometry, chromatography, and ability to support the growth of Escherichia coli 15 T(-). Residual dimer was determined by a UV-reversibility assay. The G-values for dimer breakage were approximately equal in N(2) and O(2). At low γ-doses, about two thymines were produced per dimer broken in N(2), whereas only about one thymine appeared per dimer broken in O(2). For dimer irradiated in frozen solution, the yield of thymine was at least 100 times less than in liquid.